Synthesis of fluorescent phenylethanethiolated gold nanoclusters via pseudo-AGR method. Issue 39 (23rd September 2015) - Yao, Chuanhao; Tian, Shubo; Liao, Lingwen; Liu, Xinfeng; Xia, Nan; Yan, Nan; Gan, Zibao; Wu, Zhikun
Abstract : A pseudo-AGR method was introduced to synthesize unexpected fluorescent gold nanoclusters protected by phenylethanethiolate. Abstract : It is well known that the fluorescence of metal nanoclusters is strongly dependent of the protecting ligand and reports of phenylethanethiolated metal nanoclusters with distinct fluorescence are rare. Herein, a fluorescent phenylethanethiolated gold nanocluster is synthesized using an unexpected pseudo-AGR method (AGR: anti-galvanic reduction). The cluster is precisely determined to be Au24 (SC2 H4 Ph)20 by isotope-resolved mass spectroscopy in tandem with thermogravimetric analysis (TGA). The fluorescence comparison between Au24 (SC2 H4 Ph)20, Au25 (SC2 H4 Ph)18, Au38 (SC2 H4 Ph)24 and Au144 (SC2 H4 Ph)60 is also presented. The finding of the fluorescent phenylethanethiolated gold nanocluster in this work has important implication for future study on the fluorescence of metal nanoclusters.